Downwind coning concept rotor for a 25 MW offshore wind turbine. (August 2020) - Qin, Chao (Chris); Loth, Eric; Zalkind, Daniel S.; Pao, Lucy Y.; Yao, Shulong; Griffith, D. Todd; Selig, Michael S.; Damiani, Rick
Abstract: The size of offshore wind turbines over the next decade is expected to continually increase due to reduced balance of station costs per MW and also the higher wind energy at increased altitudes that can lead to higher capacity factors. However, there are challenges that may limit the degree of upscaling which is possible. In this paper, a two-bladed downwind turbine system is upscaled from 13.2 MW to 25 MW, by redesigning aerodynamics, structures, and controls. In particular, three 25 MW rotors have been developed: V1 is the upscaled model, V2 is a partial redesigned model, and V3 is a fully redesigned model. Despite their radically large sizes, it is found that these 25 MW turbine rotors satisfy this limited set of design drivers at the rated condition and that larger blade lengths are possible with cone-wise load-alignment. In addition, flapwise morphing (varying the cone angle with a wind-speed schedule) is investigated in terms of minimizing mean and fluctuating root bending loads using steady inflow proxies for the maximum and damage equivalent load moments. The resulting series of 25 MW rotors, which are the largest ever designed, can be a useful baseline for further development and assessment. Highlights: Two-bladed downwind turbine system rated at 25 MW is upscaled and designed. The 25 MW models are developed with aerodynamics, structural, and control redesign. They satisfy the design requirements to operate at high coning angles in simulations. Morphing is firstly considered in terms of a detailed flapwise and edgewise loads. Blade segmentation and outboard pitching may be the key at this extreme-scale.